Codesigning enhanced models of care for Northern Australian Aboriginal and Torres Strait Islander youth with type 2 diabetes: study protocol - Louise Maple-Brown; Alex Brown; Peter Azzopardi; Natasha Freeman; Jonathan E Shaw; Vicki O'Donnell; Christine Connors; Elizabeth Davis; Angela Titmuss; Renae Kirkham; John Boffa; Elna Ellis; et al. (BMJ Open, 2024)
Introduction Premature onset of type 2 diabetes and excess mortality are critical issues internationally, particularly in Indigenous populations. There is an urgent need for developmentally appropriate and culturally safe models of care. We describe the methods for the codesign, implementation and evaluation of enhanced models of care with Aboriginal and Torres Strait Islander youth living with type 2 diabetes across Northern Australia.Methods and analysis Our mixed-methods approach is informed by the principles of codesign. Across eight sites in four regions, the project brings together the lived experience of Aboriginal and Torres Strait Islander young people (aged 10–25) with type 2 diabetes, their families and communities, and health professionals providing diabetes care through a structured yet flexible codesign process. Participants will help identify and collaborate in the development of a range of multifaceted improvements to current models of care. These may include addressing needs identified in our formative work such as the development of screening and management guidelines, referral pathways, peer support networks, diabetes information resources and training for health professionals in youth type 2 diabetes management. The codesign process will adopt a range of methods including qualitative interviews, focus group discussions, art-based methods and healthcare systems assessments. A developmental evaluation approach will be used to create and refine the components and principles of enhanced models of care. We anticipate that this codesign study will produce new theoretical insights and practice frameworks, resources and approaches for age-appropriate, culturally safe models of care.Ethics and dissemination The study design was developed in collaboration with Aboriginal and Torres Strait Islander and non-Indigenous researchers, health professionals and health service managers and has received ethical approval across all sites. A range of outputs will be produced to disseminate findings to participants, other stakeholders and the scholarly community using creative and traditional formats.